Type I T cells sensitize treatment refractory tumors to chemotherapy through inhibition of oncogenic signaling pathways. Issue 3 (24th March 2021) - Cecil, Denise; Park, Kyong Hwa; Curtis, Benjamin; Corulli, Lauren; Disis, Mary (Nora)
Abstract : Background: The most common clinical outcome observed after treatment with immune checkpoint inhibitor antibodies is disease stabilization. Using vaccines to generate high levels of tumor antigen-specific T-helper 1 (Th1), we show that tumors not eradicated by vaccination demonstrate prolonged disease stabilization. We evaluated the mechanism by which type I T cells inhibit disease progression and potentially influence the subsequent clinical response to standard therapy in treatment refractory cancers. Methods: We employed a meta-analysis of studies with tumor growth from four different vaccines in two different mammary cancer models. The T-cell subtype and cytokine essential for vaccine-induced tumor inhibition was determined by in vivo neutralization studies and immunohistochemistry. The role of interferon gamma (IFN-γ) in receptor tyrosine kinase and downstream signaling was determined by immunoblotting. The role of suppressor of cytokine signaling 1 (SOCS1) on IFN-γ signaling was evaluated on SOCS1-silenced cells with immunoblotting and immunoprecipitation. The effect of vaccination on growth factor receptor signaling pathways, performed in both luminal (TgMMTVneu) and basal (C3(1)-Tag) mammary cancer models treated with paclitaxel or an anti-HER2-neu monoclonal antibody were assessed via immunoblotting. Results: Immunization with an epitope-based vaccine targeting a representative tumor antigen resulted in elevated tumor trafficking Tbet+CD4 T cells, decreased tumor proliferation and increased apoptosis compared with control vaccinated mice. The resulting disease stabilization was dependent on IFN-γ-secreting CD4 + T cells. In the presence of excess IFN-γ, SOCS1 became upregulated in tumor cells, bound insulin receptor, insulin like growth factor receptor 1 and epidermal growth factor receptor resulting in profound oncogenic signaling inhibition. Silencing SOCS1 restored growth factor receptor signaling and proliferation and prevented cell death. Similar signaling perturbations were detected in vaccinated mice developing antigen-specific Th1 cells. Vaccination synergized with standard therapies and restored disease sensitivity to treatment with both a neu-specific antibody and paclitaxel in TgMMTVneu and to paclitaxel in C3(1)-Tag. Combination of vaccination and chemotherapy or biological therapy was more effective than monotherapy alone in either model and resulted in complete resolution of disease in some individuals. Conclusions: These data suggest the clinical activity of type I T cells extends beyond direct tumor killing and immune therapies designed to increase type I T cells and could be integrated into standard chemotherapy regimens to enhance therapeutic efficacy.